3D‐Printed MOF‐Derived Hierarchically Porous Frameworks for Practical High‐Energy Density Li–O2 Batteries. (14th November 2018) - Lyu, Zhiyang; Lim, Gwendolyn J. H.; Guo, Rui; Kou, Zongkui; Wang, Tingting; Guan, Cao; Ding, Jun; Chen, Wei; Wang, John
Abstract: Aprotic Li–O2 batteries are promising candidates for next‐generation energy storage technologies owing to their high theoretical energy densities. However, their practically achievable specific energy is largely limited by the need for porous conducting matrices as cathode support and the passivation of cathode surface by the insulating Li2 O2 product. Herein, a self‐standing and hierarchically porous carbon framework is reported with Co nanoparticles embedded within developed by 3D‐printing of cobalt‐based metal–organic framework (Co‐MOF) using an extrusion‐based printer, followed by appropriate annealing. The novel self‐standing framework possesses good conductivity and necessary mechanical stability, so that it can act as a porous conducting matrix. Moreover, the porous framework consists of abundant micrometer‐sized pores formed between Co‐MOF‐derived carbon flakes and meso‐ and micropores formed within the flakes, which together significantly benefit the efficient deposition of Li2 O2 particles and facilitate their decomposition due to the confinement of insulating Li2 O2 within the pores and the presence of Co electrocatalysts. Therefore, the self‐standing porous architecture significantly enhances the cell's practical specific energy, achieving a high value of 798 Wh kg −1 cell . This study provides an effective approach to increase the practical specific energy for Li–O2 batteries by constructing 3D‐printed framework cathodes. Abstract : 3D‐printed cobalt (Co)‐based metal–organic framework–derived carbon framework with a hierarchically porous network and embedded with Co nanocatalysts is developed via a extrusion‐based method. The self‐standing framework acts as a porous conducting matrix for the cathode, and the desired micrometer‐sized pores formed between carbon flakes efficiently accumulate Li2 O2 particles, which together significantly increases the practical specific energy of Li–O2 batteries.